2015
DOI: 10.1097/md.0000000000001914
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Aerobic Endurance and Muscular Strength in Substance Use Disorder Patients

Abstract: Although substance use disorder (SUD) patients are documented to have an inactive lifestyle, which is associated with cardiovascular disease, other lifestyle-related diseases and premature death, evidence regarding their aerobic endurance and muscular strength is limited. Therefore, the authors aimed to evaluate directly assessed maximal oxygen consumption, walking efficiency, as well as maximal strength in a group of SUD patients.A total of 44 SUD patients in residential treatment, 31 men (31 ± 8 years) and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 38 publications
2
23
0
2
Order By: Relevance
“…Additionally, healthy women have a mathematically somewhat worse efficiency contrasted to healthy men, contributing to the difficulty of reaching statistically difference in women. Interestingly, the reduction seen in men is similar to what is observed in substance use disorder patients, 35 but somewhat higher compared to previous reports from in-and outpatients with schizophrenia suggesting an efficiency between 17% and 20%. 11,44 The lower walking efficiency implies that patients with schizophrenia overconsume energy during certain physical activities or basic activities that involve walking.…”
Section: Functional Performance and Schizophreniasupporting
confidence: 80%
See 1 more Smart Citation
“…Additionally, healthy women have a mathematically somewhat worse efficiency contrasted to healthy men, contributing to the difficulty of reaching statistically difference in women. Interestingly, the reduction seen in men is similar to what is observed in substance use disorder patients, 35 but somewhat higher compared to previous reports from in-and outpatients with schizophrenia suggesting an efficiency between 17% and 20%. 11,44 The lower walking efficiency implies that patients with schizophrenia overconsume energy during certain physical activities or basic activities that involve walking.…”
Section: Functional Performance and Schizophreniasupporting
confidence: 80%
“…This likely puts them at a significantly higher risk of premature death as low muscle strength previously has been associated with higher risk of death from all‐cause, cancer, and cardiovascular disease . Although data on muscle strength are limited from schizophrenia patients, the impairment is similar to what has been observed in another psychiatric patient population, substance use disorder patients, a population with similar life expectancy, and levels of inactivity . Thus, reductions in maximal muscle strength could be a general pattern within psychiatry.…”
Section: Discussionmentioning
confidence: 85%
“…Given the high correlation observed between time on treadmill and VO 2peak values in our subset of participants who completed their maximal exercise test using indirect calorimetry, we believe that the use of time on treadmill provides a valid representation of CRF levels for our entire sample. While the VO 2peak values for the men (38.4 ± 7.4 mL•kg -1 •min -1 ) and women (30.8 ± 6.3 mL•kg -1 •min -1 ) in our subset of 30 individuals are higher than those (men = 30.6 mL•kg -1 •min -1 ; women = 23.2 mL•kg -1 •min -1 ) from a younger sample of methamphetamine users (Dolezal et al, 2013), they are lower than substance using European adults (Flemmen & Wang, 2015). According to established reference values ( ACSM Guidelines for Exercise Testing and Prescription, 2010), the CRF levels observed in this study equate to the 40 th and 35 th percentiles for men and women, respectively, presenting a potentially significant health risk.…”
Section: Discussionmentioning
confidence: 60%
“…CRF has also been associated with depression (Dishman et al, 2012), schizophrenia (Scheewe, Takken, Kahn, Cahn, & Backx, 2012), and sleep (King, Oman, Brassington, Bliwise, & Haskell, 1997), which can all be impacted by stimulant use (Morgan et al, 2006). Two previous studies in substance using populations, one in methamphetamine users, reported CRF levels well below the population average (Dolezal et al, 2013; Flemmen & Wang, 2015), which may be related to the poor health conditions often observed in these individuals. However, both of these studies had relatively small sample sizes (39 and 44 individuals, respectively) creating a need for verification across a larger population of stimulant users.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation